2014
DOI: 10.5455/medscience.2014.03.8150
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of 6-weeks Military Training on Blood Hematological Parameters in Untrained Recruits in a Military University

Abstract: Freshmen officer cadets in a military

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(22 reference statements)
1
2
0
Order By: Relevance
“…It appears that these changes may influences on athletic performance, recovery and long-term compatibility (5,6). Various studies have investigated the changes of blood components following different exercise program (7,8). In line with the results of this study, Field, Gougeon and Marliss (1991) were reported double raise of White Blood Cells (WBC) number after two exhaustive stationary bike training session (9).…”
Section: Introductionsupporting
confidence: 75%
“…It appears that these changes may influences on athletic performance, recovery and long-term compatibility (5,6). Various studies have investigated the changes of blood components following different exercise program (7,8). In line with the results of this study, Field, Gougeon and Marliss (1991) were reported double raise of White Blood Cells (WBC) number after two exhaustive stationary bike training session (9).…”
Section: Introductionsupporting
confidence: 75%
“…Strenuous exercise is known to cause structural damage in the erythrocyte, resulting in hemolysis. Increasing the number of erythrocytes deformed by exercise can be reflected as an increase of mean cell volume in the circulation [ 27 ]. In this study, immediately after exercise, mean cell volume values were significantly increased and these values returned to resting levels 3 h after the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…There are some different studies in the literature which yielded mixed results of exercise on hematological values. Some studies report that aerobic and aerobic exercises affects hematological values (Ricci, Mosatti, Vitali, Vedovate & Zanotti, 1988;Schumacher et al 2000;Wu et al 2004;Karakoc, Duzova, Polat, Emre & Arabaci, 2005;Cakmakci, 2009;MohammadNajad, Kandi, Shahidi, MohammadNajad & Masoudian, 2012;Hammouda et al 2012;Koushi, Mollanovruzib & Rashidlamirc, 2013;Gnanou et al, 2014;Itagi, Veena & Patil, 2014;Findikoglu et al 2014;Profil, 2014f), Some of them found that exercise do not affect hematological values (Spiropoulos and Trakada, 2003).…”
Section: Introductionmentioning
confidence: 99%